Yield and growth characteristics of sunflower sown from August to February in Santa Maria, RS - Arno B. Heldwein; Luis H. Loose; Dionéia D. P. Lucas; Fernando D. Hinnah; Mateus P. Bortoluzzi; Ivan C. Maldaner (Revista Brasileira de Engenharia Agrícola e Ambiental)
Sunflower (Helianthus annuus L.) is an oilseed crop that can be grown in different regions and sowing dates, but not all regions and sowing dates are appropriate for the crop development. The aim of this study was to determine yield and growth characteristics of sunflower on seven sowing dates, in Santa Maria, from 2007 to 2012. Five experiments were carried out in a completely randomized factorial design with four replications. The factor "A" was monthly sowing dates from the beginning of August to February and the factor "D" was two sunflower hybrids. Capitulum diameter, maximum leaf area index, maximum height of plants, weight of thousand achenes and yield were determined. In normal or La Niña years the highest yield is reached in September sowing dates, while in El Niño years, the crop growth and yield in early sowings are affected negatively, due to heavy rainfall, soil water excess and plant diseases.